New Treatment Modalities for Neovascular Age‐Related Macular Degeneration. Issue 6 (November 2017) - Schlottmann, Patricio G.; Alezzandrini, Arturo A.; Zas, Marcelo; Rodriguez, Francisco J.; Luna, José D.; Wu, Lihteh
Abstract : Abstract: : Age‐related macular degeneration (AMD) is considered one of the main causes of severe vision loss in older adults. The neovascular form (nAMD) is an advanced stage, which is responsible for the most severe vision loss. Vascular endothelial growth factor (VEGF) is at present the main factor that leads to the development of a neovascular membrane and the increased leakage from the membrane to the retina. At present, anti‐VEGF therapy is the only treatment that achieves vision gains in many patients and halts progression in most of them. VEGF blockade can be achieved with several molecules and various treatment regimens, which have been studied with excellent results. Unfortunately, real‐world data has shown to be far less efficacious than clinical trials. This gap between clinical trials and real‐world results is an unmet medical need that supports the necessity of new treatment modalities for nAMD. Of the various treatments being studied, anti‐VEGFs of higher efficacy and longer durability are those more advanced in their development. Brolucizumab and abicipar pegol are 2 new anti‐VEGF drugs that had positive results in phase 2 studies and are being tested in phase 3 trials at present. Other promising therapies are antiangiopoietin 2 molecules, which are in phase 2 development. At earlier stages of development but with promising results are squalamine, anti‐VEGF‐C and ‐D, and gene therapy. The future will give retina specialists a broad armamentarium with which patients may achieve high visual gains for the long term with a low treatment burden.